2020
DOI: 10.1016/j.geomorph.2019.106937
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on bedrock erodibility and landscape response times upstream of an active fault

Abstract: Considerable progress has been made in modelling the response of rivers to tectonic perturbation in order to decode the tectonic signals embedded in river long profiles and planform geometry. Whilst studies have showed the importance of rock type on the morphology of rivers responding to tectonics on a local scale, these effects are often not captured in landscape evolution models. In fact, current models of fluvial response to tectonic perturbation such as active faulting require carefully collected data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 91 publications
(196 reference statements)
5
32
0
Order By: Relevance
“…∼6.2 × 10 −6 m 1−2 m yr −1 . These results are consistent with the previously reported range of erodibility estimates known for the area for comparable rock types (Table 3; Pechlivanidou et al, 2019;Zondervan et al, 2020).…”
Section: Erodibility (K)supporting
confidence: 93%
See 2 more Smart Citations
“…∼6.2 × 10 −6 m 1−2 m yr −1 . These results are consistent with the previously reported range of erodibility estimates known for the area for comparable rock types (Table 3; Pechlivanidou et al, 2019;Zondervan et al, 2020).…”
Section: Erodibility (K)supporting
confidence: 93%
“…This assertion is supported by river profiles and hillslope gradient maps that do not show distinct stepped morphologies (beyond those artifacts in the DEM) that are commonly observed in horizontal or subhorizontal strata with strong differences in erodibility (Figures 2e and S1). Furthermore, several other geomorphic studies assume that comparable units within Corinth maintain spatially and temporally uniform erodibility and generate results that mimic geological observations (Pechlivanidou et al, 2019;Watkins et al, 2018;Zondervan et al, 2020). As noted above, there are small amounts of valley aggradation upstream in the river network associated with back tilting due to flexural uplift (Fernández-Blanco et al, 2020), but such deposits are spatially limited.…”
Section: Spatially and Temporally Uniform Erodibilitymentioning
confidence: 80%
See 1 more Smart Citation
“…In the west rift, westward of the reversed drainages, the largest catchments have river morphologies that are similar albeit less marked, with steep gorges and narrow valleys in a broad upwarped zone that separates a low‐gradient, low‐relief landscape upstream from a steeper, high‐relief landscape downstream (e.g., Seger & Alexander, ; Zondervan et al, ). As in the rift center, west rift sequences of offlapping stranded deltas become younger coastward (Ford et al, , ; Seger & Alexander, ).…”
Section: Corinth Rift: Early Continental Rifting Natural Laboratorymentioning
confidence: 99%
“…Recent studies focusing on lithology and fractures in bedrock channels have also revealed the importance of material strength in setting incision rates and response times of channels to base level forcings (e.g., Stock and Montgomery, 1999;Whipple and Tucker, 2002;Cook et al, 2009;Whittaker and Boulton, 2012;Forte et al, 2016;Yanites et al, 2017;DiBiase et al, 2018;Zondervan et al, 2020) as well as in setting patterns in the position and orientations of rivers (e.g., Koons et al, 2012;Roy et al, 2015;2016a, b, c;Upton et al, 2018;Scott and Wohl, 2019). Detailed field and numerical modeling studies of rivers in faulted landscapes in particular demonstrate the sensitivity of fluvial incision to gradients in erodibility between weak fault zones and the surrounding stronger bedrock (Roy et al, 2016c).…”
Section: Introductionmentioning
confidence: 99%